Material characterization of iron-based shape memory alloys for use in self-centering columns - Hong, Huanpeng; Gencturk, Bora; Saiidi, M Saiid (Smart materials and structures, 2024)
Iron-based shape memory alloys (FeSMAs) are emerging as a promising material for use in post-tensioning concrete structures to provide self-centering capabilities during a seismic event. Past experimental studies on FeSMA focused on strengthening or repairing existing structural components under gravity loading. In addition to the structural rehabilitation, FeSMA also have potential for use in self-centering columns subjected to seismic loads. However, the basic material properties, such as strength, ductility, recovery strain, actuation stress (i.e. prestress) stability, low-cycle fatigue resistance, and temperature dependence of FeSMA related to self-centering column applications have not been studied extensively to-date. To fill this knowledge gap and determine the feasibility of using FeSMA in self-centering columns, this study performed a comprehensive characterization and analysis of FeSMA both before and after actuation (i.e. thermal stimulation). The strength, ductility, energy dissipation, and recovery strain of FeSMA before actuation were tested at different temperatures from −40 °C to 50 °C. After actuation, the actuation stress, low-cycle fatigue resistance, and strain capacity of FeSMA were tested at different temperatures from −40 °C to 50 °C and prestrain levels from 4% to 30%, and under low-cycle fatigue loading with strain amplitudes from 0.5% to 1.0%. The results from this study demonstrated that FeSMA exhibit high ductility, cyclic actuation stress stability, and low-cycle fatigue resistance at temperatures from −40 °C to 50 °C. Furthermore, it was found that increasing the prestrain level can effectively increase the post-actuation strain amplitude at which the actuation stress reduces to zero. A prestrain level between 15% and 20% is recommended for application of FeSMA in self-centering columns. The research findings from this study demonstrated the feasibility of using FeSMA in self-centering columns subject to seismic loading.